Uniting Community Ecology and Evolutionary Rescue Theory: Community-Wide Rescue Leads to a Rapid Loss of Rare Species - van Eldijk, Timo J. B.; Bisschop, Karen; Etienne, Rampal S. (Frontiers in Ecology and Evolution, 2020)
Most ecological communities are facing changing environments, particularly due to global climate change. When migration is impossible, adaptation to these altered environments is necessary to survive. Yet, we have little theoretical understanding how ecological communities respond both ecologically and evolutionarily to such environmental change. Here we introduce a simple eco-evolutionary model, the Community-Wide Rescue (CWR) model, in which a community faces environmental deterioration and each species within the community is forced to undergo adaptation or become extinct. We assume that all species in the community are equivalent except for their initial abundance. This individual based simulation model thus combines community ecology and evolutionary rescue theory. We show that under Community-Wide Rescue a rapid loss of rare species occurs. This loss occurs due to competition and a limited supply of beneficial mutations. The rapid loss of rare species provides a testable prediction regarding the impact of Community-Wide Rescue on species abundance distributions in ecological communities.